Pemanfaatan Dan Pengolahan Buah Mangrove Jenis Rhizophora Mucronata Menjadi Kopi Mangrove di Desa Persiapan Empol, Sekotong, Lombok Barat - Suyantri, Eni; Pujiana, Nita; Ardila, Dinda Dwi; Fitri, Aulia; Syalsabilla, Avira Pebrina; Mabrur, Muh. Hijjul (Universitas Mataram, 2024)
The use of mangrove fruits, especially the Rhizophora mucronata type, into mangrove coffee is an innovation carried out to increase the economic value of the mangrove ecosystem in Empol Preparatory Village, Sekotong District, West Lombok Regency. The purpose of this activity is to educate the local community about the importance of maintaining the mangrove ecosystem while utilizing mangrove fruits that have not been used optimally so far. This program is carried out through socialization and practice of mangrove coffee making that involves the community directly. As a result, the community gained new knowledge and skills in processing mangrove fruits into products of economic value, which is expected to increase their income. This mangrove coffee product has the potential to be mass-produced and become a superior product in the region.